Oral health providers' views of oral health promotion in Jazan, Saudi Arabia: a qualitative study - Mosa Ali Shubayr; Estie Kruger; Marc Tennant (BMC, 2023)
Abstract Background Oral health promotion (OHP) is a crucial aspect of dental care, as it aims to improve and protect oral health of individuals. This study aimed to qualitatively explore views of oral health providers in Jazan, Saudi Arabia, on their perceptions of their responsibilities for OHP, as well as the barriers and potential opportunities for implementing health promotion in dental practice. Methods A convenience sample of 11 oral health providers from Ministry of Health (MOH) facilities were recruited and participated in virtual one-on-one semi-structured interviews, which were transcribed and analyzed using inductive thematic analysis with N-Vivo software. Results The results showed that the providers recognized the significant role and responsibility of OHP in improving oral health. However, several barriers hindered their OHP efforts, including a lack of training, funding, time, and a lack of interest in OHP. Potential opportunities for improvement included increasing recruitment of new oral health providers and educators, developing more training programs for providers and the community, and expanding support in terms of finances and logistics. Conclusion The findings of the study suggest that oral health providers are aware of OHP, but that both patients and organizations will need to shift their behaviours and perspectives for OHP to be successfully implemented. Further research on OHP in the Kingdom of Saudi Arabia (KSA) is needed to validate these findings.